Photovoice in EFL Essay Writing: Student - Militansina (English Language Education Department, Universitas Majalengka, 2023)
Although research regarding writing for English as a foreign language has been much discussed and reported, little empirical evidence addresses photovoice, which documents the student teachers’ learning experience on essay writing in the Asian context. To fill this void, this article reports on a case study investigating the student teachers' learning experience on essay writing using photovoice. The research findings indicate that integrating photovoice in EFL writing instruction positively influenced student teachers' self-awareness, motivation, and reflective learning habits. Student teachers reported increased engagement in the writing process, improved self-evaluation and peer evaluation skills, and a greater sense of agency in addressing writing challenges, ultimately leading to enhanced writing proficiency and confidence. This study reveals the positive impact of photovoice in EFL writing instruction for Asian student teachers, enhancing self-awareness, motivation, and reflective learning habits and improving writing proficiency and confidence.